2020
DOI: 10.1002/acm2.13044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of setup errors on multi‐isocenter volumetric modulated arc therapy for craniospinal irradiation

Abstract: Multi-isocenter volumetric modulated arc therapy (VMAT) is recommended for craniospinal irradiation (CSI) to smooth the dose distribution in the junction regions relying solely on inverse optimization. However, few studies have measured the dosimetric impact of setup errors on this multi-isocenter VMAT in the junction areas. The purpose of this study is to evaluate the impact of positional errors during VMAT CSI with twodimension (2D) and three-dimension (3D) dosimetric measurements. A total of 20 patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(55 reference statements)
1
10
0
2
Order By: Relevance
“…also concluded that accuracy will not be deteriorated when larger errors of >5 mm were simulated 7 . The findings of these publications 4,7,17 along with acceptable dose variation of up to 5 ‐mm positional errors supports our clinical decisions.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…also concluded that accuracy will not be deteriorated when larger errors of >5 mm were simulated 7 . The findings of these publications 4,7,17 along with acceptable dose variation of up to 5 ‐mm positional errors supports our clinical decisions.…”
Section: Discussionsupporting
confidence: 77%
“…Zhou et al. also reports that positional errors within 3 mm have little impact on dosimetry for VMAT CSI 17 and Meyer et al. also concluded that accuracy will not be deteriorated when larger errors of >5 mm were simulated 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al used the ArcCHECK and EBT3 film dosimeters to perform CSI plan QA, analyzing the impact of setup errors. They presented the pass rate ranging from 85% to 95% on the gamma analysis with 3% dose deviation and multiples distance to agreement (1 mm to 8 mm) criteria [ 30 ]. Nguyen et al used an electronic portal-imaging device panel as the detector and EPIDQA software with gamma analysis 3%/3 mm and accuracy above 90% as the pass criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Modern TPSs allow the combined optimization of multiple isocentres and, thus, homogeneity constraints will automatically include junction areas. This issue has been extensively addressed in the context of CSI, which has even more challenging homogeneity requirements (296)(297)(298). Special complexity in TBI results from isocentre extension over two separate datasets with different patient orientations.…”
Section: Isocentric Highly Conformal Tbi Techniquesmentioning
confidence: 99%